Shipboard ADCP current measurements (38 kHz) during RV SONNE cruise SO309 - Robert Kopte; André Freiwald; Evgenia A Bazhenova; Alissa Bach; Sam Davidson (PANGAEA, 2025)
Current velocities of the upper water column along the cruise track of R/V Sonne cruise SO309 were collected by a vessel-mounted 38 kHz RDI Ocean Surveyor ADCP. The ADCP transducer was located at 6.0 m below the water line. The instrument was operated in narrowband mode (WM10) with a bin size of 32.00 m, a blanking distance of 16.00 m, and a total of 50 bins, covering the depth range between 54.0 m and 1622.0 m. Attitude data from the ship extquotesingles motion reference unit were used by the data acquisition software VmDAS internally to convert ADCP beam velocities to geographic coordinates. The Python toolbox OSADCP (version 2.0.2) was used for data post-processing. Acoustic Interferences were identified based on outliers in the ADCP echo intensity data. Echo intensity data were cleaned accordingly and affected velocity cells were flagged to be removed prior ensemble-averaging. The ship extquotesingles velocity was calculated from position fixes obtained by the Global Navigation Satellite System (GNSS), taking into account lever arms of ADCP transducer and GNSS antenna. Accuracy of the derived water velocities mainly depends on the quality of the position fixes and the ship extquotesingles heading data. Further errors stem from a misalignment of the transducer with the ship extquotesingles centerline. Data processing included water track calibration of the misalignment angle (-0.1015° +/- 0.8157°) and scale factor (1.0021 +/- 0.0140) of the measured velocities. The velocity data were averaged in time using an average interval of 180 s. Depth cells with ensemble-averaged percent-good values below 25% are marked as extquotesinglebad data extquotesingle. Furthermore, the time series of cell 1 to 3 are flagged as extquotesinglepotentially correctable bad data extquotesingle because of velocities biases most likely caused by transducer ringing.